2012
DOI: 10.1183/09031936.00069812
|View full text |Cite
|
Sign up to set email alerts
|

Survival of lung adenocarcinoma patients with malignant pleural effusion

Abstract: In the era of targeted therapy, the association between lung adenocarcinoma patient survival and malignant pleural effusions (MPEs) remains unclear. This study investigated the clinical characteristics, survival and epidermal growth factor receptor (EGFR) gene (EGFR) mutation status of lung adenocarcinoma patients with MPE.From June 2005 to December 2010, consecutive pleural effusions were collected prospectively. Patient clinical characteristics, EGFR mutation status, and overall survival were analysed.We col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
88
7
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 49 publications
15
88
7
4
Order By: Relevance
“…Wu et al (17) reported that lung adenocarcinoma patients with Stage IV disease and malignant PE at the time of diagnosis have poorer OS times than patients who develop malignant PE following disease progression. However, the difference was only statistically significant in patients with distant metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al (17) reported that lung adenocarcinoma patients with Stage IV disease and malignant PE at the time of diagnosis have poorer OS times than patients who develop malignant PE following disease progression. However, the difference was only statistically significant in patients with distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicities of EGFR-TKIs are decreased compared with those of cytotoxic drugs and patients can achieve a good quality of life while using them (8,12). In patients treated with first generation EGFR-TKIs, brain, bone and liver metastasis and pleural effusion (PE) predicted a poorer prognosis compared with patients without these metastasis (13)(14)(15)(16)(17). However, few reports concern the association between the site of metastasis and prognosis (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…No treatment exists, and palliative attempts may cause further morbidity and mortality (19,20). MPE was recently reclassified as a separate stage of lung cancer, since it was acknowledged to represent a distinct form of metastatic disease with very short survival (18,21,22). Simultaneously, we and others used mouse models to hypothesize that MPE is primarily an immune-and vascularMast cells (MCs) have been identified in various tumors; however, the role of these cells in tumorigenesis remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the group with pleuritis discovered at the first consultation had a higher rate of EGFR mutation positivity, especially for the Exon21 L858R mutation. 7) However, opinions vary regarding the relationship between carcinomatous pleuritis and pleural lavage cytology findings. Higashiyama et al 11) reported that carcinomatous pleuritis at the site of recurrence was more frequent in their lavage cytology-positive group (23.5% vs 2.4%).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] It has also been shown that EGFR gene mutation-positive lung cancer patients frequently have malignant pleural effusion 6) that develops during the postoperative follow-up course. 7) Thus, an association between EGFR gene mutation positivity and carcinomatous pleuritis has been pointed out. Although patients with positive pleural lavage cytology findings do not always develop carcinomatous pleuritis, pleural lavage cytology positivity and carcinomatous pleuritis might not be identical.…”
mentioning
confidence: 99%